RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN LELANG MENGGUNAKAN METODE SIMPLE MULTY ATTRIBUTE RATING TECHNIQUE (SMART) - Hendra, Syaiful; Azhar, Ryfial; Risaldi Pata’Dungan, Adi; Ngemba, Hajra Rasmita; Laila, Rahmah (Fakultas Teknik, Universitas Tadulako, 2021)
Auction is a process that starts from the moment someone is about to sell an item until a price agreement is reached or until the auction is stopped, so that the item is not auctioned or sold. In the auction evaluation section, there is a problem, namely when there are many assessment documents for the goods to be auctioned, making the assessment hampered because they are still using the manual method, by assessing one by one document of the goods to be auctioned and then the results of the assessment are compared with other data items to determine which ones are eligible for auction, so that requires a longer process to determine the items eligible for auction. This study uses the SMART method for its decision support system method. This study using 15 criteria in determining decisions. The result of this research is that the decision support system designed or built is successful in selecting auction-worthy vehicles, by implementing the SMART method and running well. Determination of eligibility for auction vehicles must meet predetermined criteria, there are 15 criteria in the assessment of auction vehicles. System testing is carried out by comparing manual calculations with calculations using the system resulting in a 100% accuracy percentage of the 61 test data entered into the system.